2007
DOI: 10.1097/01.ta.0000236054.42254.b7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aprotinin on Brain Ischemic-Reperfusion Injury After Hemorrhagic Shock in Rats: An Experimental Study

Abstract: The results suggest that the systemic use of aprotinin in ischemic neural tissue prevents reperfusion injury and also protects the morphologic, functional, and biochemical integrity of the neural tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…It is known that aprotinin reduces apoptosis. For example Eser reported that aprotinin decreased apoptotic cell death after brain ischemia [28 Eser]. We also have confirmed that aprotinin reduces apoptotic cell death caused by serum deprivation at the concentration of 100 KIU/mL using a cell culture model (data not shown).…”
Section: Discussionsupporting
confidence: 78%
“…It is known that aprotinin reduces apoptosis. For example Eser reported that aprotinin decreased apoptotic cell death after brain ischemia [28 Eser]. We also have confirmed that aprotinin reduces apoptotic cell death caused by serum deprivation at the concentration of 100 KIU/mL using a cell culture model (data not shown).…”
Section: Discussionsupporting
confidence: 78%
“…Cell death is considered one of the mechanisms by which hemorrhagic shock may lead to organ dysfunction or failure [1,29]. When cell death was inhibited, both organ function and survival rates were significantly improved after prolonged hemorrhage and resuscitation [30].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is a situation where all tissues cannot receive enough blood and oxygen for their normal metabolic activities, and following reperfusion often exacerbates the injury [1]. Despite improvements in intensive care medicine, the mortality of massive surgical blood loss and its complications remain very high [2].…”
Section: Introductionmentioning
confidence: 99%
“…A desirable outcome would be to combine thrombolytic properties without hemorrhage or compromise of BBB permeability; however, this outcome remains elusive. However, plasmin inhibitors are neuroprotective, and the plasmin/PAR1 axis identified here may be explored further as a therapeutic target [17, 4951]. …”
Section: Discussionmentioning
confidence: 99%